Flood Disaster Relief Operation: A Systematic Literature Review - Febrina; Runtuk, Johan K.; Maukar, Anastasia L.; Puspitarini, Erri W. (TALENTA Publisher, 2022)
A flood is natural disaster that often occurs in many regions. Flood has a significant impact on the nature conditions, local communities, and regional economic losses. The flood can happen due to a damaged environmental system; therefore, it needs deeper study and extra effort to prevent it. Thus, an appropriate and right Disaster Relief Operation (DRO) is needed in responding to flood disaster. In this research, 50 articles categorized in